Cardiovascular risk assessment tools in Asia. Issue 4 (4th January 2022) - Zhang, Yuqing; Miao, Huanhuan; Chia, Yook‐Chin; Buranakitjaroen, Peera; Siddique, Saulat; Shin, Jinho; Turana, Yuda; Park, Sungha; Tsoi, Kelvin; Chen, Chen‐Huan; Cheng, Hao‐Min; Li, Yan; et al.
Abstract: Cardiovascular disease (CVD) is becoming the most important burden to health care systems in most part of the world, especially in Asia. Aiming at identifying high risk individuals and tailoring preventive treatment, many cardiovascular risk assessment tools have been established and most of them were developed in Western countries. However, these cardiovascular risk assessment tools cannot be used interchangeably without recalibration because of the different risk factor profiles (ie, greater absolute burden of hypertension and lower level of total‐cholesterol in Asians and higher prevalence of metabolic disorders in South Asians) and different CVD profiles (higher ratio of stroke/coronary heart disease in Asians) between Western and Asian populations. Original risk models such as Prediction for ASCVD Risk in China (China‐PAR) and Japan Arteriosclerosis Longitudinal Study (JALS) score have been developed and well validated for specific countries, while most of countries/regions in Asia are using established models. Due to higher incidence of stroke in Asians, risk factors like hypertension should weigh more in cardiovascular risk assessment comparing with Western populations, but their actual proportions should be based on CVD profiles in specific countries/regions. The authors encourage the development of new cardiovascular risk assessment tools for Asians, if possible. Still, modifying established models with native epidemiological data of risk factor as well as CVD is acceptable in regions where health care resources are insufficient.